Pictilisib Enhances the Antitumor Effect of Doxorubicin and Prevents Tumor-Mediated Bone Destruction by Blockade of PI3K/AKT Pathway - Liang, Chao; Yu, Xijiao; Xiong, Naping; Zhang, Zhichang; Sun, Zhenyu; Dong, Yang (Frontiers in Oncology, 2021)
Despite advances in neoadjuvant chemotherapy, outcomes for patients with osteosarcoma resistant to first-line chemotherapy have been dismal for decades. There is thus an urgent need to develop novel targeted drugs to effectively treat refractory osteosarcoma. Dysregulation in the PI3K/AKT pathway has been observed during the development of osteosarcoma. Herein, we first evaluated p-AKT (Ser473) expression levels in osteosarcoma tissue using high-throughput tissue microarrays. Then, we demonstrated the role of pictilisib, a novel potent PI3K inhibitor, in osteosarcoma and related osteolysis. Functional studies of pictilisib in osteosarcoma cell lines and bone marrow-derived macrophages were performed in vitro. Patient-derived xenografts and orthotopic mouse models were used to assess the effects of pictilisib in vivo. The results showed that positive p-AKT expression levels after neoadjuvant chemotherapy were significantly associated with tumor cell necrosis rate. Pictilisib effectively inhibited the proliferation of osteosarcoma through G0/G1-S phase cell cycle arrest, and enhanced the sensitivity of osteosarcoma to doxorubicin, although it failed to induce cell apoptosis alone. In addition, pictilisib inhibited differentiation of osteoclasts and bone resorption in vitro and tumor-related osteolysis in vivo via inhibition of the PI3K/AKT/GSK3β and NF-κB pathways. Pictilisib combined with conventional chemotherapy drugs represents a potential treatment strategy to suppress tumor growth and bone destruction in p-AKT-positive patients.